ANALISIS KEMAMPUAN PROBLEM SOLVING KONSEP FISIKA PADA MATERI IMPULS MOMENTUM PADA SISWA SMA MUHAMMADIYAH 1 DEMAK - Nurhayati, Titik (EduFisika: Jurnal Pendidikan Fisika, 2021)
This study aims to analyze the problem solving skills of class X students of SMA Muhammadiyah 1 Demak in the academic year 2020-2021. In this study, there were 13 students who had taken the impulse momentum material. This study used an instrument in the form of essay questions consisting of 5 questions, 3 types of conceptual questions and then 2 questions in the form of arithmetic or mathematical questions. The data were analyzed using the method of describing the results of students' answers which led to indicators of problem solving abilities which included the ability to identify problems, the ability to define and represent problems, the ability to explore strategies, the ability to apply strategies, and the ability to evaluate solutions. The results of this study are in the form of students' problem solving abilities on the physics concepts contained in the momentum impulse material. From the results of the answer analysis, the tenth grade students of SMA Muhammadiyah 1 Demak are good at solving problems but in wording they are still not right. With the results of this study, it is necessary to develop problem-solving skills in class X students of SMA Muhammadiyah 1 Demak.